2014
DOI: 10.1111/nbu.12086
|View full text |Cite
|
Sign up to set email alerts
|

Dairy and cardiovascular health: Friend or foe?

Abstract: Cardiovascular disease (CVD) prevalence at a global level is predicted to increase substantially over the next decade due to the increasing ageing population and incidence of obesity. Hence, there is an urgent requirement to focus on modifiable contributors to CVD risk, including a high dietary intake of saturated fatty acids (SFA). As an important source of SFA in the UK diet, milk and dairy products are often targeted for SFA reduction. The current paper acknowledges that milk is a complex food and that simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 82 publications
1
41
0
Order By: Relevance
“…Moreover, the inclusion of animal-derived products adds diversity to plant-based diets, providing an important source of many essential nutrients, the dietary requirements of which would be more difficult to meet by plant-based diets. However, the potential health impacts of animal-derived foods, and more specifically Proceedings of the Nutrition Society milk and dairy consumption, have been questioned owing to their high saturated fat content (for review, see (3) ). However, emerging epidemiological evidence supports the beneficial effects of milk and dairy consumption on health, particularly cardiometabolic health (4)(5)(6) .…”
Section: Dairy Protein: Metabolic Health: Blood Pressure: Vascular Fumentioning
confidence: 99%
“…Moreover, the inclusion of animal-derived products adds diversity to plant-based diets, providing an important source of many essential nutrients, the dietary requirements of which would be more difficult to meet by plant-based diets. However, the potential health impacts of animal-derived foods, and more specifically Proceedings of the Nutrition Society milk and dairy consumption, have been questioned owing to their high saturated fat content (for review, see (3) ). However, emerging epidemiological evidence supports the beneficial effects of milk and dairy consumption on health, particularly cardiometabolic health (4)(5)(6) .…”
Section: Dairy Protein: Metabolic Health: Blood Pressure: Vascular Fumentioning
confidence: 99%
“…A new RCT (RESET; ClinicalTrials. gov NCT02089035) (88) is investigating this in depth and preliminary results from a recent meta-analysis of three prospective studies indicated that whilst dairy fat was not significantly associated with CVD, models which estimated the effect of replacing 5 % of energy from dairy fat with vegetable fat predicted a 10 % reduction in CVD risk (89) . The dairy foods that supplied the fat were not specified and data on this are needed to more fully understand this outcome.…”
Section: Dairy Products and Blood Lipidsmentioning
confidence: 99%
“…For some of them, such as saturated lipids, lactose and some casein forms, the mechanisms of atherogenic effect were documented (Laugesen et al, 2003;Segall, 1994Segall, , 2002Warensjo et al, 2010;Markey et al, 2014). Other ingredients or products, like some enzymes, low-weight partially digested peptides and non-protein nitrogen compounds, are still in the serious observations, as it was published by Awasthi et al (2012), and .…”
Section: Figure 1 Beneficial and Possible Harmful Milk Ingredients Amentioning
confidence: 81%
“…That is why the dairy industry has in recent years worked intensively on manufacturing the low-fat, fat-modified or fat-free milk, what involved filtering out the fat from the milk or supplementation of polyunsaturated fatty acids (Markey et al, 2014;Ferreiro et al, 2015). Above mentioned articles may suggest that low-SFA or fat-modified milk should be preferred, regarding cardio-metabolic benefit, when compared to commercially available whole milk dairy products.…”
Section: Milk Fatsmentioning
confidence: 99%